Storytelling Branding in Practice - Fog, Klaus; Budtz, Christian; Munch, Philip; Blanchette, Stephen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
As a business concept “storytelling” has had a significant impact on how companies can build strong corporate cultures and credible brands. Yet many corporations are still confused as to how exactly storytelling can make a difference: Why should we tell stories at all? What makes a good story? And how do we tell it in a way that advances our company both culturally and fiscally while strengthening our brand? The second edition of this successful book presents ten new case studies. Written by practitioners for practitioners and students and filled with simple tools for putting corporate storytelling into practice, it provides knowledge and inspiration for using storytelling as a strategic tool for releasing your company’s potential.
Branding Through Storytelling -- Branding Through Storytelling -- The Toolbox -- The Four Elements of Storytelling -- Storytelling in Business -- The Company Core Story -- Authentic Raw Material for Storytelling -- Storytelling Applied -- Storytelling as a Management Tool -- Storytelling in Advertising -- When Storytelling Becomes Dialogue -- The Media as a Storytelling Partner -- Tearing Down the Walls.
Keywords: Marketing; Marketing